A retórica da imagem na grande reportagem transmídia - de Souza Ventura, Mauro [UNESP]; de Lucena Ito, Liliane [UNESP] (Universidade Estadual de Londrina, 2016)
This article assumes that, in journalism, pictures can fulfill several functions, including informing and persuading too, approaching to those produced for advertising purposes. Based on the methodology proposed by Umberto Eco in The absent structure, this text analyzes photographs produced for a digital report. The results indicate the existence of articulations similar to those seen in advertisement pieces, however, with some differences.
The rhetoric of the image in the transmedia news report
Keywords: Illustrative photos; Journalism; TAB; Transmedia story